Positive electrode active material and lithium secondary battery including same

By modifying the surface of lithium manganese-based oxide, reducing its surface resistance and forming a spinel phase, the disadvantages of lithium secondary batteries in electrochemical performance and stability are solved, and the life and stability of lithium secondary batteries are significantly improved.

CN119890248APending Publication Date: 2025-04-25ECOPRO BM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411228196.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-25
Filing Date
2024-09-03
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The lithium-rich lithium manganese-based oxides used in existing lithium secondary batteries have disadvantages in electrochemical performance and stability, especially in terms of rate performance and lifetime characteristics.

Method used

By modifying the surface of lithium manganese-based oxide, its surface resistance is reduced and spinel phase is formed to improve electrochemical performance and stability.

Benefits of technology

The modified lithium manganese-based oxide can inhibit the redox of Mn4+, reduce side reactions with the electrolyte, prolong the life of the lithium secondary battery and improve its stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890248A_ABST
    Figure CN119890248A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material and a lithium secondary battery comprising the same, and more particularly, to a positive electrode active material and a lithium secondary battery comprising the same, the positive electrode active material being a positive electrode active material comprising a lithium-rich lithium manganese-based oxide, the surface resistance of the lithium-manganese-based oxide can be reduced by surface modification of the lithium-manganese-based oxide, so that the life characteristics of a lithium secondary battery using the lithium-manganese-based oxide as a positive electrode active material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material and a lithium secondary battery including the same. More specifically, the present invention relates to a positive electrode active material and a lithium secondary battery including the same. The positive electrode active material is a positive electrode active material including a lithium-rich lithium manganese-based oxide, which can reduce the surface resistance of the lithium manganese-based oxide by surface modification of the lithium manganese-based oxide, thereby improving the life characteristics of the lithium secondary battery using the lithium manganese-based oxide as the positive electrode active material. Background Art

[0002] Batteries use materials that can undergo electrochemical reactions at the positive and negative electrodes to store electrical energy. A typical example of such batteries is a lithium secondary battery that stores electrical energy through the chemical potential difference when lithium ions are inserted / released between the positive and negative electrodes.

[0003] The lithium secondary battery is prepared by using a substance capable of reversibly inserting and extracting lithium ions as a positive electrode active material and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.

[0004] Representative materials used as positive electrode active materials for lithium secondary batteries include lithium composite oxides. Examples of the lithium composite oxides include LiCoO 2 、LiMN 2 O 4 、LiNiO 2 、LiMnO 2 Or complex oxides of nickel, cobalt, manganese or aluminum, etc.

[0005] Among the above positive electrode active materials, LiCoO 2 It is the most widely used due to its excellent life characteristics and charge and discharge efficiency, but its price competitiveness is limited due to the high price of cobalt used as a raw material due to resource limitations.

[0006] LiMnO 2 、LiMN 2 O 4 Lithium manganese-based oxides such as LiNiO have the advantages of excellent thermal stability and low price, but have the problems of small capacity and poor high temperature characteristics. 2 The cathode active material exhibits battery characteristics of high discharge capacity, but is difficult to synthesize due to the problem of cation mixing between lithium and transition metals, and thus has a big problem in rate performance.

[0007] Furthermore, depending on the severity of the cation mixing, a large amount of lithium by-products are produced, most of which are LiOH and Li 2CO 3 Therefore, when preparing the positive electrode slurry, it may cause gelation, or may become a cause of gas generation due to repeated charge and discharge after the electrode is prepared. In addition, the residual Li in the above lithium by-products 2 CO 3 The increase in the swelling of the monomer causes a reduction in the service life.

[0008] Various candidate materials are being discussed for compensating for the shortcomings of these existing positive electrode active materials.

[0009] For example, research is underway to use lithium-rich manganese-based oxides containing excess manganese in transition metals and a lithium content greater than the total content of transition metals as positive electrode active materials for lithium secondary batteries. Such lithium-rich manganese-based oxides are also called overlithi ated layered oxides (OLO).

[0010] Although the above OLO has the advantage of showing high capacity under high voltage working environment in theory, in reality, due to the excessive manganese contained in the oxide, its conductivity is relatively low, so there is a disadvantage that the rate performance of the lithium secondary battery using OLO is low. As mentioned above, when the rate performance is low, the charge / discharge capacity and life efficiency (cycle capacity retention) deteriorate during the cycle of the lithium secondary battery.

[0011] In order to solve the above problems, research has been conducted to change the composition of OLO, but these attempts have not yet reached commercialization level. Summary of the invention

[0012] Technical issues

[0013] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles plays a leading role in the market, and the demand for positive electrode active materials used in lithium secondary batteries is also constantly changing.

[0014] For example, in the prior art, lithium secondary batteries using lithium iron phosphate (LFP) are mainly used from the viewpoint of ensuring safety, etc., but recently, the use of nickel-based lithium composite oxides having a large energy capacity per unit weight compared to LFP has been expanded (of course, at present, relatively cheap LFP is still used to reduce costs).

[0015] In addition, nickel-based lithium composite oxides, which are mainly used as positive electrode active materials for high-capacity lithium secondary batteries in recent years, must use ternary metal elements such as nickel, cobalt and manganese or nickel, cobalt and aluminum. However, since cobalt is not only unstable in supply and demand but also too expensive compared to other raw materials, a positive electrode active material with a new composition that can reduce the cobalt content or does not contain cobalt is needed.

[0016] Taking the whole situation into consideration, although lithium-rich lithium manganese-based oxides can meet the expectations of the above-mentioned market, the above-mentioned lithium manganese-based oxides still have the limitation of lacking electrochemical performance or stability in replacing commercial positive electrode active materials such as ternary lithium composite oxides composed of nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA).

[0017] For example, the inventors of the present invention have confirmed that lithium manganese-based oxides are more likely to have transition metals eluted from the particle surface during repeated charge and discharge than ternary lithium composite oxides. In particular, manganese contained in excess in lithium manganese-based oxides is more likely to be eluted from the particle surface.

[0018] When the transition metal is eluted from the lithium manganese-based oxide, the eluted transition metal may react with the electrolyte on the surface of the lithium manganese-based oxide to form impurities. The impurities not only increase the surface resistance of the lithium manganese-based oxide, but also become the cause of reducing the insertion / extraction efficiency of lithium ions through the lithium manganese-based oxide.

[0019] As mentioned above, compared with other types of commercially available positive electrode active materials, existing lithium-rich lithium manganese-based oxides have disadvantages in electrochemical properties and / or stability. However, the inventors of the present invention have found that by modifying the surface of the lithium manganese-based oxide, the Mn in the lithium manganese-based oxide can be suppressed. 4+ Anion redox to Mn 2+ , thereby stabilizing the unstable surface of the lithium manganese-based oxide, thereby improving the life characteristics of a lithium secondary battery using the lithium manganese-based oxide as a positive electrode active material.

[0020] The inventors of the present invention have discovered that by modifying the surface of the above-mentioned lithium manganese-based oxide, not only can the side reaction between the above-mentioned lithium manganese-based oxide and the electrolyte be reduced by forming a physical barrier between the above-mentioned lithium manganese-based oxide and the electrolyte, but also when a spinel phase is formed in at least a portion of the surface of the above-mentioned lithium manganese-based oxide through the above-mentioned surface modification, the above-mentioned spinel phase can stabilize the unstable surface of the above-mentioned lithium manganese-based oxide, thereby improving the life characteristics of the lithium secondary battery using the above-mentioned lithium manganese-based oxide as the positive electrode active material.

[0021] In addition, the inventors of the present invention have found that when the surface resistance of the lithium manganese-based oxide is reduced by surface modification of the lithium manganese-based oxide, the early degradation of the lithium manganese-based oxide can be prevented and the life characteristics of the lithium secondary battery using the lithium manganese-based oxide as the positive electrode active material can be further improved.

[0022] Therefore, the object of the present invention is to provide a positive electrode active material, which is a positive electrode active material including a lithium-rich lithium manganese-based oxide, which can reduce the surface resistance of the above-mentioned lithium manganese-based oxide by surface modification of the above-mentioned lithium manganese-based oxide using molybdenum, so as to improve the life characteristics of a lithium secondary battery using the above-mentioned lithium manganese-based oxide as a positive electrode active material.

[0023] Another object of the present invention is to provide a positive electrode comprising a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material defined herein.

[0024] In addition, an object of the present invention is to provide a lithium secondary battery that prevents a reduction in life due to excess lithium and manganese present in existing OLOs by using the cathode defined herein.

[0025] Solutions to the problem

[0026] According to one aspect of the present invention for solving the above-mentioned technical problems, there is provided a positive electrode active material including a lithium manganese-based oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are solid-dissolved.

[0027] In the commonly commercialized ternary lithium composite oxides composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA), the phase belonging to the R3-m space group exists as a single phase. However, the lithium-rich lithium manganese-based oxide defined in this article is characterized in that the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group are solid-dissolved.

[0028] In one embodiment, the lithium manganese-based oxide may be represented by the following Chemical Formula 1.

[0029] [Chemical formula 1]

[0030] r 2 MnO 3-c X' c ·(1-r)Li a M1 x M2 y O 2-b X b

[0031] (wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, M2 does not overlap with M1, X and X' are each independently a halogen capable of replacing at least a portion of the oxygen present in the above-mentioned lithium manganese-based oxide, <r≤0.7、0<a≤1、0≤b≤0.1、0≤c≤0.1、0<x≤1、0≤y<1、0<x+y≤1)

[0032] In addition, the lithium manganese-based oxide may further include a spinel phase belonging to the Fd-3m space group. Therefore, the lithium manganese-based oxide may be a solid solution of a phase belonging to the C2 / m space group, a phase belonging to the R3-m space group, and a spinel phase belonging to the Fd-3m space group.

[0033] In one embodiment, the lithium manganese-based oxide can be represented by the following Chemical Formula 2.

[0034] [Chemical formula 2]

[0035] (1-z){rLi 2 MnO 3-c X' c ·(1-r)Li a M1 x M2 y O 2-b X b}·zLi(Li d Mn 2-d-e M3 e ) 4-g X" g

[0036] (wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, M2 and M1 do not overlap, M3 is at least one selected from Ni, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, X, X' and X" are each independently a halogen capable of replacing at least a portion of the oxygen present in the above-mentioned lithium manganese-based oxide, <r≤0.7、0<a≤1、0≤b≤0.1、0≤c≤0.1、0<x≤1、0≤y<1、0<x+y≤1、0<z≤0.5、0≤d≤1、0<e≤1、0≤g≤0.1)

[0037] The lithium manganese-based oxide may be a core-shell particle including a core and a shell, wherein a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are solid-dissolved in the core, and the shell is present in at least a portion of the surface of the core and contains a spinel phase belonging to the Fd-3m space group. At this time, since the core and the shell are solid-dissolved in each other, there is no inter-particle boundary between the core and the shell.

[0038] Additionally, a molybdenum-containing coating may be present on at least a portion of the surface of the shell portion.

[0039] Furthermore, according to another aspect of the present invention, a positive electrode comprising the positive electrode active material defined herein is provided. Specifically, the positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, and the positive electrode active material exists in the positive electrode active material layer.

[0040] In addition, according to another aspect of the present invention, a lithium secondary battery comprising the positive electrode defined herein is provided. Specifically, the lithium secondary battery may comprise the positive electrode defined herein, a negative electrode, a separation membrane between the positive electrode and the negative electrode, and an electrolyte.

[0041] Effects of the Invention

[0042] According to the present invention, the limitations of existing lithium-rich lithium manganese-based oxides which are still inferior in electrochemical performance and / or stability compared with commercial ternary lithium composite oxides composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) can be improved.

[0043] Specifically, according to the present invention, by modifying the surface of the lithium manganese-based oxide, the Mn in the lithium manganese-based oxide can be suppressed. 4+ Oxidized by anions to Mn 2+ , thereby stabilizing the unstable surface of the above-mentioned lithium manganese-based oxide.

[0044] OLOs such as the above-mentioned lithium manganese-based oxide have the advantage of exhibiting high capacity under high voltage working environment. At this time, the higher the working voltage, the higher the possibility of side reactions between the above-mentioned lithium manganese-based oxide and the above-mentioned electrolyte. Considering this, it is important to reduce the side reactions between the above-mentioned lithium manganese-based oxide and the above-mentioned electrolyte.

[0045] Therefore, as the side reaction between the lithium manganese-based oxide and the electrolyte is reduced, the stability and life of the lithium secondary battery using the lithium manganese-based oxide as the positive electrode active material can be improved. In particular, the positive electrode active material that suppresses the side reaction of the electrolyte can drive the lithium secondary battery at a higher voltage. At this time, if the lithium manganese-based oxide is surface-modified, a spinel phase can be formed on at least a portion of the surface of the lithium manganese-based oxide.

[0046] In addition, according to the present invention, the surface resistance of the lithium manganese-based oxide is reduced by surface modification of the lithium manganese-based oxide to prevent premature degradation of the lithium manganese-based oxide, and further, the life characteristics of the lithium secondary battery using the lithium manganese-based oxide as the positive electrode active material can be improved.

[0047] In addition to the above-described effects, specific effects of the present invention will be described while explaining specific details for implementing the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 A surface SEM image and surface EDS analysis results (target element: Mo) of the lithium manganese-based oxide (secondary particles) according to Example 3 are shown.

[0049] Figure 2 A line-scanning direction in a cross-sectional SEM image of the lithium manganese-based oxide according to Example 3 is shown.

[0050] Figure 3 A surface SEM image and surface EDS analysis results (target element: Mo) of the lithium manganese-based oxide (secondary particles) according to Example 4 are shown. DETAILED DESCRIPTION

[0051] Specific terms are defined herein for ease of understanding. Unless specifically defined herein, scientific terms and technical terms used herein should have the meanings commonly understood by those skilled in the art. In addition, it should be understood that as used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form, and vice versa.

[0052] Hereinafter, a positive electrode active material including a lithium-rich lithium manganese-based oxide and a lithium secondary battery including the positive electrode active material according to the present invention will be described in more detail.

[0053] Positive active material

[0054] According to one aspect of the present invention, there is provided a positive electrode active material, the positive electrode active material comprising a lithium manganese-based oxide in which a phase belonging to a C2 / m space group and a phase belonging to an R3-m space group are solid-dissolved.

[0055] The phase belonging to the C2 / m space group and the phase belonging to the R3-m space group can be distinguished not only by the composition of each phase, but also by the specific peaks of each phase during XRD analysis. For example, the characteristic peak of the phase belonging to the C2 / m space group may appear in the region of 2θ=20.8±1°, and the characteristic peak of the phase belonging to the R3-m space group may appear in the region of 2θ=18.6±1°.

[0056] The lithium manganese-based oxide is a composite oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are solid-dissolved, and the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group coexist in the lithium manganese-based oxide. In addition, the lithium manganese-based oxide and the composite oxide having a spinel crystal structure belonging to the Fd-3m space group (for example, LiMN 2 O 4 Or an oxide having a similar composition thereto).

[0057] The lithium manganese-based oxide contains at least lithium, manganese and a transition metal. The transition metal may include at least one selected from nickel, cobalt and aluminum. In addition, the lithium manganese-based oxide may include lithium, nickel and manganese, and may optionally further include a transition metal other than nickel.

[0058] At this time, the content of lithium present in the above-mentioned lithium manganese-based oxide is greater than the sum of the contents of other transition metals (generally, the molar ratio of lithium to all metal elements except lithium in the lithium manganese-based oxide (lithium / metal molar ratio (Li / Metal molar ratio) is greater than 1), so it is also called lithium-rich layered oxide (overlithiated layered oxide; OLO).

[0059] In addition, since the content of manganese in the lithium manganese-based oxide is greater than the content of other transition metals, the lithium manganese-based oxide is also called a layered oxide with excess lithium and manganese.

[0060] Generally speaking, considering that the manganese content in the total metal elements other than lithium in the commercial nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) ternary lithium composite oxide is less than 20 mol%, the above-mentioned lithium manganese-based oxide has a relatively high ratio of manganese in the total metal elements (for example, more than 50 mol%, more than 52 mol%, more than 53 mol% or more than 55 mol%) compared with the commercial ternary lithium composite oxide.

[0061] Furthermore, considering that the content of nickel in the total metal elements other than lithium in the commercialized nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) ternary lithium composite oxide is more than 60 mol% (more than 80 mol% in the case of high-nickel lithium composite oxides), the above-mentioned lithium manganese-based oxide has a relatively low ratio of nickel in the total metal elements (for example, less than 50 mol%, less than 48 mol%, less than 46 mol%, less than 45 mol%, less than 44 mol%, less than 42 mol% or less than 40 mol%) compared with the commercialized ternary lithium composite oxide.

[0062] There is also a difference that the lithium / metal molar ratio measured from the lithium manganese-based oxide defined herein is greater than the lithium / metal molar ratio of a ternary lithium composite oxide such as nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA). For example, the lithium / metal molar ratio of a ternary lithium composite oxide such as nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA) appears to be close to 1. On the other hand, the lithium / metal molar ratio of the lithium manganese-based oxide defined herein is greater than 1, preferably 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5.

[0063] Therefore, herein, the lithium manganese-based oxide may be defined as a composite oxide in which the manganese content in the metal elements other than lithium is 50 mol % or more, or may be defined as a composite oxide in which the manganese content in the metal elements other than lithium is 50 mol % or more and the nickel content is less than 50 mol %.

[0064] In addition, the lithium manganese-based oxide herein has a molar ratio of lithium to the total metal elements other than lithium greater than 1, or is 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5, and is defined as a composite oxide in which the manganese content in the total metal elements other than lithium is 50 mol% or more, or a composite oxide in which the molar ratio of lithium to the total metal elements other than lithium is greater than 1, or is 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5, the manganese content in the total metal elements other than lithium is 50 mol% or more, and the nickel content is less than 50 mol%.

[0065] Despite the above-mentioned difference in composition, the above-mentioned lithium manganese-based oxide can also be used as a composite metal oxide capable of intercalating / deintercalating lithium ions.

[0066] The lithium composite oxide contained in the positive electrode active material as defined herein may be present as particles including at least one primary particle.

[0067] When the lithium manganese-based oxide exists as a single primary particle, the lithium composite oxide may be referred to as a single particle. On the other hand, when the lithium manganese-based oxide exists as an aggregate formed by agglomerating a plurality of primary particles, the lithium composite oxide may be referred to as a secondary particle.

[0068] The positive electrode active material may include at least one selected from the group consisting of a lithium manganese-based oxide present as a single particle and a lithium manganese-based oxide present as a secondary particle formed by agglomerating a plurality of primary particles.

[0069] The primary particles constituting the above-mentioned lithium manganese-based oxide may have a rod (rod) shape, an elliptical shape and / or an irregular shape. In addition, unless specifically designed during the manufacturing process, primary particles of various shapes exist in the same positive electrode active material. In addition, the above-mentioned primary particles refer to particle units that do not appear to have grain boundaries when observed with a scanning electron microscope at a magnification of 5000 to 20000 times.

[0070] The average particle size of the primary particles constituting the lithium manganese-based oxide defined herein may be 0.05 μm to 5 μm, 0.05 μm to 1.0 μm, 0.1 μm to 1.0 μm, or 0.25 μm to 0.75 μm. At this time, as the average particle size of the primary particles, the average value of the length in the major axis direction and the length in the minor axis direction of the primary particles ([major axis length + minor axis length] / 2) may be used.

[0071] When the average particle size of the primary particles is less than 0.05 μm, the specific surface area of ​​the lithium manganese-based oxide (secondary particles) composed of the primary particles is large. In this case, the possibility of causing a side reaction between the lithium manganese-based oxide and the electrolyte during storage or operation of the lithium secondary battery increases.

[0072] On the other hand, when the average particle size of the primary particles is greater than 5 μm, the growth of the primary particles is excessively induced, so the diffusion path of lithium ions in the primary particles also becomes longer. When the diffusion path of lithium ions in the primary particles is too long, the mobility of lithium ions in the primary particles and the diffusivity of lithium ions through the primary particles are reduced, which becomes a cause of increasing the resistance of the lithium composite oxide (secondary particles) composed of the primary particles.

[0073] Therefore, in order to prevent the mobility of lithium ions in the above-mentioned primary particles and the diffusivity of lithium ions through the above-mentioned primary particles from decreasing while reducing the specific surface area of ​​the above-mentioned lithium manganese-based oxide, the average particle size of the above-mentioned primary particles is preferably 0.05μm to 5μm, 0.05μm to 1.0μm, 0.1μm to 1.0μm or 0.25μm to 0.75μm.

[0074] When the lithium manganese-based oxide exists as secondary particles formed by the aggregation of multiple primary particles, the average particle size of the secondary particles can be 0.5μm to 15μm, 1.0μm to 15μm, 2.0μm to 15μm, 3.0μm to 15μm, 4.0μm to 15μm or 5.0μm to 15μm. The average particle size of the secondary particles can vary according to the number of the primary particles constituting the secondary particles. The average particle size (D50) of the secondary particles can be measured using a laser diffraction method. For example, after the secondary particles are dispersed in a dispersion medium, they are introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), irradiated with ultrasonic waves of about 28kHz at a power of 60W, and then after obtaining a volume cumulative particle size distribution chart, the particle size equivalent to 50% of the volume cumulative amount is obtained to achieve measurement.

[0075] Unless otherwise defined, the term "surface of the primary particle" as used herein refers to the outer surface of the primary particle exposed to the outside. Similarly, the term "surface of the secondary particle" as used herein refers to the outer surface of the secondary particle exposed to the outside. In this case, the "surface of the secondary particle" formed by the agglomeration of multiple primary particles is equivalent to the exposed surface of the primary particle existing on the surface of the secondary particle.

[0076] In addition, unless otherwise defined, the term "surface portion of a particle" as used herein refers to a region relatively close to the "outermost surface" of a particle, and "center portion of a particle" refers to a region relatively close to the "exact center" of a particle compared to the above-mentioned "surface portion". Therefore, the "surface portion of a primary particle" refers to a region relatively close to the "outermost surface" of the above-mentioned primary particle, and the "center portion of a primary particle" refers to a region relatively close to the "exact center" of the above-mentioned primary particle compared to the above-mentioned "surface portion". Similarly, the "surface portion of a secondary particle" refers to a region relatively close to the "outermost surface" of the above-mentioned secondary particle, and the "center portion of a secondary particle" refers to a region relatively close to the "exact center" of the above-mentioned secondary particle compared to the above-mentioned "surface portion".

[0077] At this time, a region other than the “surface portion of the particle” within any particle can be defined as the “center portion of the particle”.

[0078] For example, when the radius of the primary particle is r, the region at a distance of 0r to 0.5r from the surface of the primary particle can be defined as the surface portion of the primary particle, and the region at a distance of 0r to 0.5r from the exact center of the primary particle can be defined as the central portion of the primary particle. If the radius of the primary particle is 0.5 μm, the surface portion of the primary particle can be defined as the region at a distance of 0 μm to 0.25 μm from the surface of the primary particle, and the central portion of the primary particle can be defined as the region at a distance of 0 μm to 0.25 μm from the exact center of the primary particle.

[0079] In addition, as needed, when the radius of the above-mentioned primary particle is r, the area with a distance of 0r to 0.1r or 0r to 0.2r from the surface of the above-mentioned primary particle can be defined as the surface part of the above-mentioned primary particle, and the area with a distance of 0r to 0.2r or 0r to 0.5r from the exact center of the above-mentioned primary particle can be defined as the central part of the above-mentioned primary particle.

[0080] Similarly, when the radius of the secondary particle is r, the region at a distance of 0r to 0.5r from the surface of the secondary particle can be defined as the surface portion of the secondary particle, and the region at a distance of 0r to 0.5r from the exact center of the secondary particle can be defined as the central portion of the secondary particle. If the radius of the secondary particle is 2.0 μm, the surface portion of the secondary particle can be defined as the region at a distance of 0 μm to 1.0 μm from the surface of the secondary particle, and the central portion of the secondary particle can be defined as the region at a distance of 0 μm to 1.0 μm from the exact center of the secondary particle.

[0081] In addition, as needed, when the radius of the above-mentioned secondary particle is r, the region with a distance of 0r to 0.1r or 0r to 0.2r from the surface of the above-mentioned secondary particle can be defined as the surface portion of the above-mentioned secondary particle, and the region with a distance of 0r to 0.2r or 0r to 0.5r from the exact center of the above-mentioned secondary particle can be defined as the central portion of the above-mentioned secondary particle.

[0082] The above-mentioned lithium manganese-based oxide defined herein may be a lithium-rich lithium manganese-based oxide represented by the following Chemical Formula 1.

[0083] [Chemical formula 1]

[0084] r 2 MnO 3-c X' c ·(1-r)Li a M1 x M2 y O 2-b X b

[0085] (0 <r≤0.7、0≤c≤0.1、0<a≤1、0≤b≤0.1、0<x≤1、0≤y<1、0<x+y≤1)

[0086] Among them, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, and M2 and M1 are not repeated.

[0087] X and X' are independently halogens that can replace at least a portion of the oxygen present in the lithium manganese-based oxide. As the types of halogens that can be used as X and X', F, Cl, Br and / or I can be used with reference to the periodic table, and preferably F can be used.

[0088] In the above Chemical Formula 1, when M1 is Ni, M2 may include Mn, and when M1 is Mn, M2 may include Ni. In addition, when M1 is Ni and Mn, M2 may not exist, or, if present, may be an element other than Ni and Mn.

[0089] That is, when M1 is Ni, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd (preferably at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably at least one selected from Co, P, B, Si, Ti, Zr and W, and even more preferably at least one selected from P, B and Si) and Mn.

[0090] When M1 is Mn, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd (preferably at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably at least one selected from Co, P, B, Si, Ti, Zr and W, even more preferably at least one selected from P, B and Si) and Ni.

[0091] When M1 is Ni and Mn, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, preferably, may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably, may include at least one selected from Co, P, B, Si, Ti, Zr and W, even more preferably, may include at least one selected from P, B and Si.

[0092] The lithium manganese-based oxide represented by the above chemical formula 1 may optionally include cobalt. In addition, when the above lithium manganese-based oxide includes cobalt, the molar number of the above cobalt relative to the molar number of the entire metal element in the above lithium manganese-based oxide may be 20% or less, preferably, 15% or less, and more preferably, 10% or less. In another case, the lithium manganese-based oxide represented by the above chemical formula 1 may have a cobalt-free composition that does not contain cobalt.

[0093] The lithium / metal molar ratio measured from the lithium manganese-based oxide represented by the above chemical formula 1 may be greater than 1, preferably, it may be 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5. Only when the lithium / metal molar ratio measured from the above lithium manganese-based oxide is at least greater than 1, a lithium-rich lithium manganese-based oxide can be formed. In addition, in order to allow the above lithium manganese-based oxide to properly form a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group, and at the same time exert a high capacity under a high voltage working environment, the lithium / metal molar ratio of the above lithium manganese-based oxide is preferably 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5.

[0094] In addition, in order to properly form a solid solution in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are solid-dissolved, the content of manganese in the total metal elements other than lithium present in the lithium manganese-based oxide represented by the above chemical formula 1 is preferably 50 mol% or more. In order for the above lithium manganese-based oxide to have an OLO characteristic showing a high capacity under a high voltage operating environment, the content of manganese in the total metal elements other than lithium present in the above lithium manganese-based oxide may be 50 mol% or more and less than 80 mol%, 51 mol% or more and less than 80 mol%, 52 mol% or more and less than 80 mol%, 53 mol% or more and less than 80 mol%, 54 mol% or more and less than 80 mol%, 55 mol% or more and less than 80 mol%, 50 mol% or more and less than 75 mol%, 51 mol% or more and less than 75 mol%, 52 mol% or more and less than 75 mol%, 53 mol% or more and less than 75 mol%, 54 mol% or more and less than 75 mol%, 55 mol% or more and less than 75 mol%, When the manganese content in the above-mentioned lithium manganese-based oxide exceeds 80 mol%, a phase change may occur during the formation and / or operation of the lithium secondary battery due to the movement of the transition metal (especially manganese) in the above-mentioned lithium manganese-based oxide. This phase change occurs at random positions in the above-mentioned lithium manganese-based oxide, thereby causing a reduction in charge / discharge capacity or voltage decay during the cycle of the lithium secondary battery using the above-mentioned lithium manganese-based oxide as the positive electrode active material. In addition, when the manganese content in the above-mentioned lithium manganese-based oxide exceeds 80 mol%, it may be difficult to fully produce a phase belonging to the R3-m space group.

[0095] In order to properly form a solid solution in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are solid-dissolved, the content of nickel in the entire metal elements other than lithium present in the lithium manganese-based oxide represented by the above Chemical Formula 1 can be less than 50 mol%, less than 48 mol%, less than 46 mol%, less than 45 mol%, less than 44 mol%, less than 42 mol% or less than 40 mol%.

[0096] When the nickel content in the above-mentioned lithium manganese-based oxide is above 50 mol%, it is difficult to fully form the C2 / m phase, or the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group may not form a sufficient solid solution, resulting in phase separation during the formation and / or operation of the lithium secondary battery.

[0097] Generally, in a commercially available ternary lithium composite oxide composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA), a phase belonging to the R3-m space group exists as a single-phase.

[0098] On the other hand, the lithium-rich lithium manganese-based oxide represented by the above chemical formula 1 is composed of rLi 2 MnO 3-c X' c The oxides of the phase belonging to the C2 / m space group (hereinafter referred to as "C2 / m phase") and (1-r)Li a M1 x M2 y O 2-b X b The composite oxide exists in which the oxide of the phase belonging to the R3-m space group (hereinafter referred to as "R3-m phase") is solid-solved. In the present application, the solid-solution of the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group means that the oxide of the C2 / m phase and the oxide of the R3-m phase exist in a state of forming a solid solution.

[0099] In this case, a composite oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are simply physically and / or chemically combined or attached does not correspond to a solid solution as defined herein.

[0100] For example, a metal oxide having a phase belonging to the C2 / m space group whose surface is coated with a metal oxide belonging to the R3-m space group by mixing a metal oxide having a phase belonging to the C2 / m space group and a metal oxide having a phase belonging to the R3-m space group does not correspond to the solid solution defined in this article.

[0101] In addition, in the lithium manganese-based oxide represented by the above chemical formula 1, when r exceeds 0.7, Li 2 MnO 3-c X' c The ratio of R3-m phase oxide to C2-m phase oxide is excessively increased, which may increase the irreversible capacity and resistance of the positive electrode active material, thereby reducing the discharge capacity. That is, in order to fully activate the C2 / m phase oxide with relatively high resistance in the above-mentioned lithium manganese-based oxide to improve the surface dynamics, the R3-m phase oxide is preferably present in a predetermined ratio or more.

[0102] In addition, the lithium manganese-based oxide may also include a spinel phase belonging to the Fd-3m space group. In this case, the lithium manganese-based oxide may exist as a solid solution of a phase belonging to the C2 / m space group, a phase belonging to the R3-m space group, and a spinel phase belonging to the Fd-3m space group.

[0103] The spinel phase can be formed by surface modification of the lithium manganese-based oxide. By modifying the surface of the lithium manganese-based oxide, the spinel phase is formed on at least a portion of the surface of the lithium manganese-based oxide (i.e., a portion or all of the surface of the lithium manganese-based oxide), thereby suppressing the Mn 4+ Oxidized by anions to Mn 2+ , thereby stabilizing the unstable surface in the above-mentioned lithium manganese-based oxide.

[0104] In addition, since the spinel phase is formed on the surface of the lithium manganese-based oxide, it is different from a phase formed by phase transformation occurring at random positions in the lithium manganese-based oxide due to the movement of transition metals (especially manganese) in the lithium manganese-based oxide.

[0105] The lithium manganese-based oxide formed by solid solution of a phase belonging to the C2 / m space group, a phase belonging to the R3-m space group, and a spinel phase belonging to the Fd-3m space group can be represented by the following Chemical Formula 2.

[0106] [Chemical formula 2]

[0107] (1-z){rLi 2 MnO 3-c X' c ·(1-r)Li a M1 x M2 y O 2-b X b}·zLi(Li d Mn 2-d-e M3 e ) 4-g X" g

[0108] (0 <r≤0.7、0≤c≤0.1、0<a≤1、0≤b≤0.1、0<x≤1、0≤y<1、0<x+y≤1、0<z≤0.5、0≤d≤1、0<e≤1、0≤g≤0.1)

[0109] Among them, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, and M2 and M1 are not repeated.

[0110] X, X' and X" are each independently a halogen capable of replacing at least a portion of the oxygen present in the lithium manganese-based oxide. As the type of halogen that can be used as X and X', with reference to the periodic table, F, Cl, Br and / or I can be used, and preferably F can be used.

[0111] In the lithium manganese-based oxide represented by the above Chemical Formula 2, the description about the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group is the same as that of the lithium manganese-based oxide represented by Chemical Formula 1.

[0112] M3 is at least one selected from Ni, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd. Preferably, M3 is Ni, and may optionally include at least one element selected from Ni, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd.

[0113] In the above chemical formula 2, the composition of the spinel phase belonging to the Fd-3m space group is zLi(Li d Mn 2-d-e M3 e ) 4- g X" g For example, the spinel phase can be composed of LiMn 1.5 Ni 0.5 O 4 express.

[0114] In the lithium manganese-based oxide represented by the above chemical formula 2, when z exceeds 0.5, the ratio of the spinel phase in the above lithium manganese-based oxide increases excessively, thereby possibly increasing the irreversible capacity and resistance of the positive electrode active material, thereby possibly reducing the discharge capacity.

[0115] In one embodiment, the lithium manganese-based oxide may be a core-shell particle including a core and a shell, wherein the core contains a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group in a solid solution, and the shell exists in at least a portion of the surface of the core and contains a spinel phase belonging to the Fd-3m space group. At this time, since the core and the shell are mutually solid-dissolved, no grain boundary can exist between the core and the shell.

[0116] When the lithium manganese-based oxide is a core-shell particle, the ratio of the core to the total volume of the lithium manganese-based oxide may be 1% to 99%, preferably 30% to 99%, and more preferably 50% to 99%.

[0117] In the case where the core is a secondary particle formed by agglomeration of a plurality of primary particles, the shell having the spinel phase may be present in at least a portion of the surface of the primary particle. Therefore, the primary particle may exist as an independent particle of a spinel phase solid solution belonging to a C2 / m space group, a R3-m space group, and a Fd-3m space group.

[0118] Furthermore, in the case where the core is a secondary particle formed by agglomeration of a plurality of primary particles, the shell containing the spinel phase may exist in at least a portion of the surface of the secondary particle. That is, the primary particles existing inside the secondary particle and / or in the center of the secondary particle exist as particles in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are solid-dissolved, and the primary particles existing on the outermost surface of the secondary particle and / or in an area close to the outermost surface of the secondary particle (the surface of the secondary particle) exist as particles in which a phase belonging to the C2 / m space group, a phase belonging to the R3-m space group, and a spinel phase belonging to the Fd-3m space group are solid-dissolved.

[0119] In addition, the shell portion in which the spinel phase exists may exist in the form of diffusion from the surface of the secondary particle to the center of the secondary particle along the boundary between the primary particles. Therefore, the ratio of the spinel phase in the lithium manganese-based oxide may be higher at the surface of the secondary particle than at the center of the secondary particle. Similarly, the ratio of primary particles of the spinel phase solid solution belonging to the C2 / m space group, the R3-m space group, and the Fd-3m space group may be higher at the surface of the secondary particle than at the center of the secondary particle.

[0120] Herein, the spinel phase may be formed by surface modification of the lithium manganese-based oxide using molybdenum. Through the surface modification, a molybdenum-containing coating may be formed on at least a portion of the surface of the lithium manganese-based oxide.

[0121] When the molybdenum-containing coating reduces the surface resistance of the lithium manganese-based oxide, the early degradation of the lithium manganese-based oxide can be prevented, and further help improve the life characteristics of a lithium secondary battery using the lithium manganese-based oxide as a positive electrode active material. In addition, the molybdenum-containing coating can induce the formation of a spinel phase on the surface of the lithium manganese-based oxide.

[0122] The molybdenum-containing coating may include a 3 and Li 2 MoO 4 At least one of .

[0123] When the lithium manganese-based oxide exists as secondary particles formed by aggregation of a plurality of primary particles, the molybdenum may exist at a higher concentration on the surface of the secondary particles than in the interior of the secondary particles.

[0124] When the above-mentioned lithium manganese-based oxide is a core-shell particle including a core portion in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are solid dissolved, and a shell portion present in at least a portion of the surface of the above-mentioned core portion and containing a spinel phase belonging to the Fd-3m space group, the molybdenum-containing coating may be present in at least a portion of the surface of the above-mentioned shell portion.

[0125] Furthermore, when the core is a secondary particle formed by agglomeration of a plurality of primary particles, the molybdenum may be present at a higher concentration on the surface of the secondary particle than in the interior of the secondary particle. In this case, the molybdenum may form a concentration gradient that decreases from the surface of the secondary particle to the interior of the secondary particle along the interface between the primary particles.

[0126] As defined herein, when the surface-modified positive electrode active material is subjected to X-ray diffraction analysis using Cu-Kα rays, the following characteristics may be exhibited.

[0127] In one embodiment, when the positive electrode active material is subjected to X-ray diffraction analysis using Cu—Kα rays, the intensity ratio of the diffraction peaks attributed to the (003) plane and the (104) plane satisfies the following formula 1.

[0128] [Formula 1]

[0129] 1.59≤I(003) / I(104)≤2.6

[0130] I(003) / I(104) according to the above formula 1 may be 1.59 to 2.6, 1.59 to 2.5, 1.59 to 2.3, 1.591 to 2.1, or 1.591 to 2.012.

[0131] When a spinel phase belonging to the Fd-3m space group is formed in the positive electrode active material surface-modified as defined herein, the intensity of the diffraction peak attributed to the (104) plane appearing in the 2θ=43.5° to 45.0° region may be weakened.

[0132] According to the above formula 1, I(003) / I(104) greater than 2.6 means that an excessive amount of spinel phase is formed in the above lithium manganese-based oxide. In this case, as the irreversible capacity and resistance of the above positive electrode active material increase, the charge / discharge capacity and discharge capacity retention rate of the lithium secondary battery using the above lithium manganese-based oxide as the positive electrode active material may decrease.

[0133] On the other hand, according to the above formula 1, I(003) / I(104) is less than 1.59, which means that the spinel phase is almost not formed in the above lithium manganese-based oxide. In this case, due to the insufficient anion redox inhibition effect by the spinel phase, it is difficult to stabilize the unstable surface in the above lithium manganese-based oxide, thereby making it difficult to improve the life characteristics of the lithium secondary battery using the above lithium manganese-based oxide as the positive electrode active material.

[0134] Furthermore, when the positive electrode active material is subjected to X-ray diffraction analysis using Cu-Kα rays, the full width at half maximum (FWHM) of the diffraction peak attributed to the (104) plane may be 0.27 to 0.50, 0.27 to 0.40, or 0.27 to 0.382.

[0135] When a spinel phase belonging to the Fd-3m space group is formed in the surface-modified positive active material as defined herein, the full width at half maximum of the diffraction peak attributed to the (104) plane appearing in the 2θ=43.5° to 45.0° region may become larger.

[0136] The full width at half maximum of the diffraction peak attributable to the above-mentioned (104) surface is greater than 0.50, which means that an excessive amount of spinel phase is formed in the above-mentioned lithium manganese-based oxide. In this case, as the irreversible capacity and resistance of the above-mentioned positive electrode active material increase, the charge / discharge capacity and discharge capacity retention rate of the lithium secondary battery using the above-mentioned lithium manganese-based oxide as the positive electrode active material may decrease.

[0137] On the other hand, the full width at half maximum of the diffraction peak attributable to the (104) plane is less than 0.27, which means that the spinel phase is almost not formed in the lithium manganese-based oxide. In this case, due to the insufficient anion redox inhibition effect by the spinel phase, it may be difficult to stabilize the unstable surface of the lithium manganese-based oxide.

[0138] In an X-ray diffraction analysis of the positive electrode active material using Cu—Kα rays, the intensity ratio of diffraction peaks attributed to the (018) plane and the (110) plane satisfies the following formula 2.

[0139] [Formula 2]

[0140] 1.15≤I(018) / I(110)≤1.55

[0141] I(018) / I(110) according to the above formula 2 may be 1.15 to 1.55, 1.15 to 1.50, or 1.157 to 1.545.

[0142] When a spinel phase belonging to the Fd-3m space group is formed in the surface-modified positive active material according to the definition herein, the intensity of the diffraction peak attributed to the (110) plane appearing in the 2θ=64.7° to 65.5° region may be weakened.

[0143] According to the above formula 2, I(018) / I(110) greater than 1.55 means that an excessive amount of spinel phase is formed in the above lithium manganese-based oxide. In this case, as the irreversible capacity and resistance of the above positive electrode active material increase, the charge / discharge capacity and discharge capacity retention rate of the lithium secondary battery using the above lithium manganese-based oxide as the positive electrode active material may decrease.

[0144] On the other hand, according to the above formula 2, I(018) / I(110) is less than 1.15, which means that the spinel phase is almost not formed in the above lithium manganese-based oxide. In this case, due to the insufficient anion redox inhibition effect by the spinel phase, it is difficult to stabilize the unstable surface in the above lithium manganese-based oxide, thereby making it difficult to improve the life characteristics of the lithium secondary battery using the above lithium manganese-based oxide as the positive electrode active material.

[0145] That is, the surface-modified lithium manganese-based oxide as defined herein can suppress the Mn 4+ Oxidized by anions to Mn 2+ , thereby stabilizing the unstable surface of the above-mentioned lithium manganese-based oxide.

[0146] In addition, the molybdenum-containing coating and spinel phase formed on the surface of the lithium manganese-based oxide by the surface modification can be used as a barrier to prevent the occurrence of side reactions between the lithium manganese-based oxide and the electrolyte, thereby helping to improve the stability and life of the lithium secondary battery using the lithium manganese-based oxide as the positive electrode active material. In addition, according to the present invention, the surface resistance of the lithium manganese-based oxide is reduced by surface modification of the lithium manganese-based oxide to prevent premature degradation of the lithium manganese-based oxide, and further, the life characteristics of the lithium secondary battery using the lithium manganese-based oxide as the positive electrode active material can be improved.

[0147] Lithium secondary battery

[0148] According to another aspect of the present invention, a positive electrode including a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector may be provided, wherein the positive electrode active material layer may include the lithium manganese-based oxide according to various embodiments of the present invention as a positive electrode active material.

[0149] Therefore, the detailed description of the lithium manganese-based oxide will be omitted, and only the remaining components not mentioned above will be described below. In addition, for the sake of convenience, the lithium manganese-based oxide will be referred to as a positive electrode active material.

[0150] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or the surface of aluminum or stainless steel may be treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine concavoconvexities may be formed on the surface of the current collector to improve the binding force of the positive electrode active material. For example, it may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a nonwoven body.

[0151] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition including the positive electrode active material, a conductive material, and optionally a binder as required, on the positive electrode current collector.

[0152] In this case, the content of the positive electrode active material can be 80 wt % to 99 wt %, more specifically 85 wt % to 98.5 wt % relative to the total weight of the positive electrode active material layer. When the positive electrode active material is included in the above content range, excellent capacity performance can be shown, but it is not limited thereto.

[0153] The above-mentioned conductive materials are used to impart conductivity to the electrode. In the battery formed, as long as they do not cause chemical changes and have electronic conductivity, they can be used without limitation. As specific examples, graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and one of them or a mixture of two or more thereof can be used. The above-mentioned conductive material may be included in an amount of 0.1% to 15% by weight relative to the total weight of the positive electrode active material layer.

[0154] The above-mentioned binder plays a role in improving the adhesion between multiple positive electrode active material particles and the bonding force between the positive electrode active material and the collector. As a specific example, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated ethylene propylene diene rubber, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, etc., can be used. One or a mixture of two or more thereof. Relative to the total weight of the positive electrode active material layer, 0.1% to 15% by weight of the above-mentioned binder may be included.

[0155] In addition to using the above-mentioned positive electrode active material, the above-mentioned positive electrode can be prepared according to a common positive electrode preparation method. Specifically, it can be prepared by coating a positive electrode slurry composition on a positive electrode collector and then drying and rolling it. The above-mentioned positive electrode slurry composition is prepared by dissolving or dispersing the above-mentioned positive electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent.

[0156] The above-mentioned solvent may be a solvent commonly used in the art, and examples thereof include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone or water, and a mixture of one or more thereof may be used. Considering the coating thickness and preparation yield of the slurry, the amount of the above-mentioned solvent used is sufficient to dissolve or disperse the above-mentioned positive electrode active material, conductive material and binder and have a viscosity that can show excellent thickness uniformity when applied to prepare the positive electrode.

[0157] Furthermore, in another embodiment, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, and then laminating a thin film obtained by peeling the support on a positive electrode collector.

[0158] In addition, according to another aspect of the present invention, an electrochemical device comprising the positive electrode described above can be provided. Specifically, the electrochemical device described above can be a battery, a capacitor, etc., and more specifically, can be a lithium secondary battery.

[0159] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separation membrane and an electrolyte disposed between the positive electrode and the negative electrode. The positive electrode is the same as the above description, so for convenience, the specific description is omitted, and only the remaining configuration not described above is described below.

[0160] The lithium secondary battery may further include: a battery container for accommodating the electrode assembly of the positive electrode, the negative electrode and the separation membrane; and a sealing member for sealing the battery container.

[0161] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0162] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can usually have a thickness of 3 μm to 500 μm. Similar to the positive electrode current collector, the binding force of the negative electrode active material can be strengthened by forming fine concave and convex on the surface of the collector. For example, it can be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a non-woven body.

[0163] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition including the negative electrode active material and a conductive material and optionally including a binder as required on the negative electrode collector.

[0164] As the negative electrode active material, a compound capable of reversibly inserting and extracting lithium can be used. Specific examples include carbon materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; and SiO β (0<β<2), SnO 2, vanadium oxide, lithium vanadium oxide, a metal oxide capable of being doped and dedoped with lithium; or a composite containing the above metal compound and a carbon material such as a Si-C composite or a Sn-C composite, etc., and one or a mixture of two or more thereof can be used. In addition, as the above-mentioned negative electrode active material, a metal lithium film can also be used. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative low-crystalline carbon is soft carbon and hard carbon, and representative high-crystalline carbon is amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite (Kishgraphite), pyrolytic carbon (pyrolytic carbon), mesophase pitch-based carbon fiber (mesophase pitch based carbon fiber), mesophase carbon microbeads (meso-carbon microbeads), mesophase pitch (Mesophase pitches) and petroleum or coal tar pitch derived coke (petroleum or coal tar pitch derived cokes) and other high-temperature calcined carbon.

[0165] The negative electrode active material layer may contain 80 wt % to 99 wt % of the negative electrode active material, based on the total weight of the negative electrode active material layer.

[0166] The binder is a component that helps to bind the conductive material, the active material and the collector. Usually, based on the total weight of the negative electrode active material layer, 0.1 wt % to 10 wt % of the binder can be added. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber, sulfonated ethylene propylene diene rubber, styrene butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.

[0167] The conductive material is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, the conductive material can be added in an amount of 10% by weight or less, preferably 5% by weight or less. There are no particular restrictions on such conductive materials as long as they do not induce chemical changes in the corresponding battery and have conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.

[0168] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition on a negative electrode collector and drying it, wherein the negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent, or by casting the negative electrode slurry composition on a separate support and laminating a thin film obtained by peeling off the support on the negative electrode collector.

[0169] On the other hand, in the above-mentioned lithium secondary battery, the separation membrane is used to separate the negative electrode and the positive electrode and provide a mobile channel for lithium ions. As long as the separation membrane commonly used in the lithium secondary battery, it can be used without restriction, especially, preferably, for the ion movement of the electrolyte, the impedance is low and there is excellent electrolyte moisture-containing capacity. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers or their two or more layers of stacked structures. In addition, a common porous non-woven fabric can also be used, for example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, in order to ensure heat resistance or mechanical strength, a separation membrane coated with a ceramic component and a polymer substance can also be used, which can be selectively used with a single layer or multilayer structure.

[0170] Furthermore, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc. that can be used when preparing lithium secondary batteries, but are not limited thereto.

[0171] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0172] As the above-mentioned organic solvent, any organic solvent that can act as a medium for the movement of ions involved in the electrochemical reaction of the battery can be used without limitation. Specifically, as the above-mentioned organic solvent, ester solvents such as methylacetate, ethylacetate, γ-butyrolactone, ε-caprolactone, etc.; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (EPC), etc. can be used. Carbonate solvents such as nate, PC, etc.; alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (r is a straight-chain, branched or cyclic hydrocarbon group with 2 to 20 carbon atoms, which may contain a double-bonded aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane, etc. Among them, carbonate solvents are preferred, and more preferably, a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate, etc.) with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery, and low-viscosity linear carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.). In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, excellent electrolyte performance can be shown.

[0173] The lithium salt may be any compound that can provide lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF 6 、LiClO 4 、LiAsF 6 , LiBF 4 、LiSbF 6 、LiAlO 4 、LiAlCl 4 、LiCF 3 SO 3 ,LiC 4 F 9 SO 3、LiN(C 2 F 5 SO 3 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 , LiCl, LiI or LiB(C 2 O 4 ) 2 etc. Preferably, the concentration of the lithium salt is used in the range of 0.1 M to 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and thus can show excellent electrolyte performance and enable lithium ions to move efficiently.

[0174] When the electrolyte used herein is a solid electrolyte, for example, a solid inorganic electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, a nitride solid electrolyte, or a halide solid electrolyte can be used, and preferably a sulfide solid electrolyte can be used.

[0175] As the material of the sulfide-based solid electrolyte, a solid electrolyte containing Li, an X element (wherein X is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In) and S can be used. Examples of the above-mentioned sulfide-based solid electrolyte material include Li 2 SP 2 S 5 , Li 2 SP 2 S-LiX (where X is a halogen element such as I or Cl), Li 2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n are integers, Z is Ge, Zn or Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li p MO q (wherein p and q are integers, and M is P, Si, Ge, B, Al, Ga or In), etc.

[0176] The solid electrolyte, preferably a sulfide-based solid electrolyte, may be in an amorphous state, a crystalline state, or a mixed state of the amorphous state and the crystalline state.

[0177] Examples of materials for the oxide-based solid electrolyte include Li 7 La 3 Zr 2 O 12 , Li 7-x La 3 Zr 1-x Nb x O 12 , Li 7- 3x La 3 Zr 2 Al x O 12 , Li 3x La 2 / 3-x TiO 3 , Li 1+x Al x Ti 2-x (PO 4 ) 3 , Li 1+x Al x Ge 2-x (PO 4 ) 3 , Li 3 PO 4 , Li 3+x PO4-x N x (LiPON), Li 2+2x Zn 1-x GeO 4 (LISICON) etc.

[0178] The solid electrolyte may be arranged between the positive electrode and the negative electrode as a separate layer (solid electrolyte layer). In addition, the solid electrolyte may be partially contained in the positive electrode active material layer of the positive electrode independently of the solid electrolyte layer, or the solid electrolyte may be partially contained in the negative electrode active material layer of the negative electrode independently of the solid electrolyte layer.

[0179] In addition to the above electrolyte components, the electrolyte may further include one or more additives such as halogenated alkylene carbonate compounds such as bisfluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, etc., for the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity, and increasing the discharge capacity of the battery. In this case, the above additives may be included in an amount of 0.1 wt % to 5 wt % relative to the total weight of the electrolyte.

[0180] As described above, the lithium secondary battery containing the positive electrode active material of the present invention stably shows excellent discharge capacity, output characteristics and life characteristics, and can therefore be used in portable devices such as mobile phones, notebook computers, digital cameras, and electric vehicles such as hybrid electric vehicles (HEV).

[0181] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a prismatic shape, a pouch shape, a coin shape, etc. Also, preferably, the lithium secondary battery can be used not only as a battery cell used as a power source for small devices, but also as a unit battery of a medium or large battery module including a plurality of battery cells.

[0182] According to another aspect of the present invention, a battery module including the above-mentioned lithium secondary battery as a unit cell and / or a battery pack including the same may be provided.

[0183] The battery module or the battery pack can be used as a power tool; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle and a plug-in hybrid electric vehicle (PHEV); or a power source for one or more medium or large devices in a power storage system.

[0184] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are only for illustrating the present invention, and the scope of the present invention should not be construed as being limited by these examples.

[0185] Preparation Example 1. Preparation of positive electrode active material

[0186] Comparative Example 1

[0187] (a) Precursor preparation

[0188] NiSO mixed in a molar ratio of 40:60 was added to the reactor. 4 6H 2 O and MnSO 4 ·H 2 O mixed aqueous solution, NaOH and NH 4 The temperature in the reactor was maintained at 45°C, and N 2 The precursor synthesis reaction was carried out while the gas was being released. After the reaction was completed, the Ni was washed and dehydrated to obtain a Ni 0.4 Mn 0.6 (OH) 2 Precursor.

[0189] (b) First heat treatment

[0190] The precursor obtained in step (a) was heat-treated in an air atmosphere at a temperature of 550° C. for 5 hours, and then furnace-cooled to obtain a precursor in an oxide state.

[0191] (c) Second heat treatment

[0192] A mixture was prepared by mixing the precursor in an oxide state obtained in step (b) with LiOH (molar ratio of lithium / (metal other than lithium) = 1.28) as a lithium raw material substance.

[0193] Then, in O 2 The mixture was heat treated at 900° C. for 8 hours in a vacuum atmosphere, furnace cooled and classified to obtain a lithium manganese-based oxide without surface modification.

[0194] Comparative Example 2

[0195] 2.0 mol% (NH 4 ) 6 Mo 7 O 24 Add 100 ml of deionized water and stir at 300 rpm while using NH 3 ·H 2 Prepare the coating solution by adjusting the pH to 9 to 10.

[0196] After adding the lithium manganese-based oxide obtained in Comparative Example 1 to the above coating solution, stirring was performed at 300 rpm for 30 minutes, and then stirring was continued at 300 rpm at 80° C. for about 12 hours until the water evaporated. Next, a mixture was prepared by further drying at 150° C. for 12 hours.

[0197] Then, in O 2 The mixture was heat treated at 750°C for 8 hours in a carbon atmosphere, furnace cooled and classified to obtain a Li 2 MoO 4 Coated lithium manganese-based oxide.

[0198] Comparative Example 3

[0199] The lithium manganese-based oxide obtained in Comparative Example 1 was mixed with 1.0 mol% (NH 4 ) 6 Mo 7 O 24 Prepare the mixture by dry mixing.

[0200] Then, in O 2 The mixture was heat treated in a vacuum atmosphere at 600° C. for 8 hours, furnace cooled and classified to obtain a lithium manganese-based oxide.

[0201] Since the (NH 4 ) 6 Mo 7 O 24 Most of it still existed in a coarse powder state after the heat treatment and was thus removed by a classification process, confirming that no Mo-containing coating was formed on the surface of the lithium manganese-based oxide.

[0202] Example 1

[0203] 0.5 mol% (NH 4 ) 6 Mo 7 O 24Add 100 ml of deionized water and stir at 300 rpm while using NH 3 ·H 2 Prepare the coating solution by adjusting the pH to 9 to 10.

[0204] After adding the lithium manganese-based oxide obtained in Comparative Example 1 to the above coating solution, stirring was performed at 300 rpm for 30 minutes, and then stirring was continued at 300 rpm at 80° C. for about 12 hours until the water evaporated. Next, the mixture was prepared by further drying at 150° C. for 12 hours.

[0205] Then, in O 2 The mixture was heat treated at 600°C for 8 hours in an atmosphere, furnace cooled and classified to obtain a layer containing MoO 3 Coated lithium manganese-based oxide.

[0206] Example 2

[0207] 1.0 mol% (NH 4 ) 6 Mo 7 O 24 Add 100 ml of deionized water and stir at 300 rpm while using NH 3 ·H 2 Prepare the coating solution by adjusting the pH to 9 to 10.

[0208] After adding the lithium manganese-based oxide obtained in Comparative Example 1 to the above coating solution, stirring was performed at 300 rpm for 30 minutes, and then stirring was continued at 300 rpm at 80° C. for about 12 hours until the water evaporated. Next, the mixture was prepared by further drying at 150° C. for 12 hours.

[0209] Then, in O 2 The mixture was heat treated at 600°C for 8 hours in an atmosphere, furnace cooled and classified to obtain a layer containing MoO 3 Coated lithium manganese-based oxide.

[0210] Example 3

[0211] 1.5 mol% (NH 4 ) 6 Mo 7 O 24 Add 100 ml of deionized water and stir at 300 rpm while using NH 3 ·H 2 Prepare the coating solution by adjusting the pH to 9 to 10.

[0212] After adding the lithium manganese-based oxide obtained in Comparative Example 1 to the above coating solution, stirring was performed at 300 rpm for 30 minutes, and then stirring was continued at 300 rpm at 80° C. for about 12 hours until the water evaporated. Next, the mixture was prepared by further drying at 150° C. for 12 hours.

[0213] Then, in O 2 The mixture was heat treated at 600°C for 8 hours in an atmosphere, furnace cooled and classified to obtain a layer containing MoO 3 Coated lithium manganese-based oxide.

[0214] Example 4

[0215] 0.5 mol% (NH 4 ) 6 Mo 7 O 24 Add 100 ml of deionized water and stir at 300 rpm while using NH 3 ·H 2 Prepare the coating solution by adjusting the pH to 9 to 10.

[0216] After adding the lithium manganese-based oxide obtained in Comparative Example 1 to the above coating solution, stirring was performed at 300 rpm for 30 minutes, and then stirring was continued at 300 rpm at 80° C. for about 12 hours until the water evaporated. Next, the mixture was prepared by further drying at 150° C. for 12 hours.

[0217] Then, in O 2 The mixture was heat treated at 750°C for 8 hours in a carbon atmosphere, furnace cooled and classified to obtain a Li 2 MoO 4 Coated lithium manganese-based oxide.

[0218] Example 5

[0219] 1.0 mol% (NH 4 ) 6 Mo 7 O 24 Add 100 ml of deionized water and stir at 300 rpm while using NH 3 ·H 2 Prepare the coating solution by adjusting the pH to 9 to 10.

[0220] After adding the lithium manganese-based oxide obtained in Comparative Example 1 to the above coating solution, stirring was performed at 300 rpm for 30 minutes, and then stirring was continued at 300 rpm at 80° C. for about 12 hours until the water evaporated. Next, the mixture was prepared by further drying at 150° C. for 12 hours.

[0221] Then, in O 2 The mixture was heat treated at 750°C for 8 hours in a carbon atmosphere, furnace cooled and classified to obtain a Li 2 MoO 4 Coated lithium manganese-based oxide.

[0222] Comparative Example 4

[0223] The surface obtained in Example 5 contains Li 2 MoO 4 The coated lithium manganese-based oxide was added to 100 ml of deionized water and stirred at 300 rpm for 10 minutes. Subsequently, the lithium manganese-based oxide remaining after filtration was filtered and dried at 150° C. for 12 hours to obtain a final product. Since the lithium manganese-based oxide was washed with deionized water, it was confirmed that the surface of the lithium manganese-based oxide in the final product did not form a Mo-containing coating.

[0224] Preparation Example 2. Fabrication of a lithium secondary battery (half-cell)

[0225] 90 wt % of each positive electrode active material prepared according to Preparation Example 1, 5.5 wt % of carbon black and 4.5 wt % of PVDF binder were dispersed in 30 g of N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum film with a thickness of 15 μm and vacuum dried at 135° C. to prepare a positive electrode for a lithium secondary battery.

[0226] With respect to the positive electrode, a lithium foil was used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as a separation membrane, and LiPF was used in a solvent of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate mixed in a volume ratio of 2:4:4. 6 The half-cell was prepared with the electrolyte present at a concentration of 1.15M.

[0227] Preparation Example 3. Preparation of lithium secondary battery (full battery)

[0228] 90 wt % of each positive electrode active material prepared according to Preparation Example 1, 4.5 wt % of carbon black, and 5.5 wt % of PVDF binder were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry.

[0229] The positive electrode slurry was uniformly coated on an aluminum thin film with a thickness of 15 μm, and vacuum dried at 135° C., thereby preparing a positive electrode for a lithium secondary battery having a positive electrode active material layer formed thereon.

[0230] With respect to the above-mentioned positive electrode, a graphite electrode was used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as a separation membrane, and LiPF was used in a solvent of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate mixed in a volume ratio of 2:4:4. 6 The full cell was prepared with the electrolyte present at a concentration of 1.15M.

[0231] Experimental Example 1. SEM / EDS Analysis of Positive Electrode Active Material

[0232] The lithium manganese-based oxide selected from each of the positive electrode active materials according to Example 3 and Example 4 was subjected to SEM / EDS analysis to confirm the surface modification of the lithium manganese-based oxide.

[0233] Referring to FIG. 3 showing a surface SEM image and a surface EDS analysis result (target element: Mo) of a lithium manganese-based oxide (secondary particle) according to Example 3 Figure 1 and a surface SEM image and surface EDS analysis results (target element: Mo) of the lithium manganese-based oxide (secondary particles) according to Example 4 Figure 3 The lithium manganese-based oxide exists as secondary particles formed by agglomeration of multiple primary particles, confirming that the target element Mo exists on the surface of the lithium manganese-based oxide. In addition, through the EDS mapping results, it can be confirmed that the concentration of Mo on the surface of the secondary particles is higher than the concentration inside the secondary particles.

[0234] In addition, if Figure 2 As shown, after obtaining a cross-sectional SEM image of the lithium manganese-based oxide selected from the positive electrode active material according to Example 3, EDS mapping was performed on Ni, Mn and Mo as target elements, and then line scanning was performed to confirm the concentrations (atomic %) of Ni, Mn and Mo at the designated locations (①, ② and ③) in the lithium manganese-based oxide. The above measurement results are shown in the following Table 1.

[0235] Table 1

[0236]

[0237] Referring to the results in Table 1, it can be confirmed that molybdenum exists at a higher concentration on the surface of the secondary particles than inside the secondary particles.

[0238] Experimental Example 2. XRD analysis of positive electrode active material

[0239] X-ray diffraction (XRD) analysis was performed on each positive electrode active material prepared according to Preparation Example 1 to confirm the space group and coating material of the phase present in the lithium manganese-based oxide contained in the above-mentioned positive electrode active material, and to detect the peaks belonging to the (003) plane, (018) plane, (104) plane and (110) plane in the crystal plane of the above-mentioned lithium manganese-based oxide. By using Cu-Kα radiation XRD analysis was performed using a Bruker D8 Advance diffractometer.

[0240] Specifically, in the diffraction pattern obtained from the XRD analysis, the characteristic peak of the phase belonging to the C2 / m space group can appear in the 2θ=20.8±1° region, and the characteristic peak of the phase belonging to the R3-m space group can appear in the 2θ=18.6±1° region. The formation of the spinel phase belonging to the Fd-3m space group can be confirmed by the change of the characteristic peak of the (104) plane appearing in the 2θ=43.5°~45.0° region and the characteristic peak of the (110) plane appearing in the 2θ=64.7°~65.5° region.

[0241] In addition, in the diffraction pattern obtained by XRD analysis, a characteristic peak of the Mo-containing coating can be observed near 2θ=30°. 2 MoO 4 The characteristic peak of MoO may appear in the region of 2θ=29.8±0.3°, and 3 The characteristic peak may appear in the region of 2θ=30.7±0.3°.

[0242] The above XRD analysis results are shown in Tables 2 and 3 below.

[0243] Table 2

[0244]

[0245] Table 3

[0246]

[0247] When a spinel phase belonging to the Fd-3m space group is formed in the above-mentioned lithium manganese-based oxide, the characteristic peaks of the (104) plane and the (110) plane collapse. Therefore, the result of the characteristic peak of the (104) plane is calculated based on the highest intensity of the pattern appearing in the region of 2θ=43.5°~45.0°, and the result of the characteristic peak of the (110) plane is calculated based on the highest intensity of the pattern appearing in the region of 2θ=64.7°~65.5°.

[0248] Experimental Example 3. Evaluation of electrochemical characteristics of lithium secondary battery (half-cell)

[0249] The lithium secondary battery (half-cell) prepared in Preparation Example 2 was subjected to a charge / discharge experiment at 25° C., a voltage range of 2.0 V to 4.6 V, and a discharge rate of 0.1 C to 2.0 C using an electrochemical analysis device (Toyo, Toscat-3100) to measure the initial charge capacity, initial discharge capacity, initial reversible efficiency, and rate performance (discharge capacity ratio; rate capability, C-rate). For reference, in the case of Comparative Example 3, since the Li mixed with the above-mentioned lithium manganese-based oxide was 2 MoO 4 Most of it still exists in the coarse powder state after heat treatment, so it is removed by the classification process, and no Li-containing 2 MoO 4 , so Comparative Example 3 is expected to be substantially the same as Comparative Example 1, and therefore Comparative Example 3 is excluded from the electrochemical performance evaluation object of the above-mentioned half-cell.

[0250] The above measurement results are shown in Table 4 below.

[0251] Table 4

[0252]

[0253]

[0254] Referring to the half-cell evaluation results in Table 4 above, it can be seen that in the case of a lithium secondary battery using the positive electrode active material according to Comparative Example 2, an excessive amount of spinel phase is formed in the positive electrode active material, and thus the electrochemical performance is deteriorated compared to Comparative Example 1. In addition, it can be confirmed that in the case of a lithium secondary battery using the positive electrode active material according to Comparative Example 4, although the spinel phase exists in the positive electrode active material, not only the Mo-containing coating is removed by the subsequent cleaning process, but defects occur on the surface of the positive electrode active material by the cleaning process, and thus the electrochemical performance is rapidly reduced.

[0255] Experimental Example 4. Evaluation of electrochemical characteristics of lithium secondary battery (full battery)

[0256] For the lithium secondary battery (full battery) prepared in Preparation Example 3, an electrochemical analyzer (Toyo, Toscat-3100) was used to complete 6 cycles of formation at 25°C, a voltage range of 2.0V to 4.6V, and 0.2C / 0.2C, and then charged / discharged 500 times at 25°C, a voltage range of 2.0V to 4.6V, and 1C / 1C. The initial (first cycle) discharge capacity and the ratio of the discharge capacity at the 500th cycle relative to the initial discharge capacity (cycle capacity retention; capacity retention) were measured.

[0257] The above measurement results are shown in Table 5 below.

[0258] Table 5

[0259]

[0260] Referring to the results in Table 5 above, it can be confirmed that in the case of Comparative Example 1, which exhibits electrochemical performance similar to that of the embodiment in the half-cell evaluation results, the long-term life characteristics are too low compared to the embodiment. Therefore, it is confirmed that the positive electrode active material defined herein is more suitable for ensuring the long-term stable life characteristics of the lithium secondary battery than the positive electrode active material according to Comparative Example 1.

[0261] Although the embodiments of the present invention are described above, those skilled in the art will understand that various modifications and changes can be made to the present invention by adding, modifying, deleting, increasing, etc., without departing from the scope of the idea of ​​the present invention as described in the claims, and these also fall within the scope of the rights of the present invention.

Claims

1. A positive electrode active material, comprising a lithium manganese-based oxide in which a phase belonging to a C2 / m space group and a phase belonging to an R3-m space group are solid-dissolved, wherein the positive electrode active material is characterized in that: The lithium manganese-based oxide further comprises a spinel phase belonging to the Fd-3m space group, In the X-ray diffraction analysis of the positive electrode active material using Cu-Kα rays, the intensity ratio of the diffraction peaks attributed to the (003) plane and the (104) plane satisfies the following formula 1: [Formula 1] 1.59≤I(003) / I(104)≤2.6 The intensity ratio of the diffraction peaks attributable to the (018) plane and the (110) plane satisfies the following formula 2: [Formula 2] 1.15≤I(018) / I(110)≤1.

55.

2. The positive electrode active material according to claim 1, characterized in that In an X-ray diffraction analysis of the positive electrode active material using Cu—Kα rays, the full width at half maximum of the diffraction peak attributed to the (104) plane was 0.27 to 0.

50.

3. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide is represented by the following chemical formula 1: [Chemical formula 1] rLi2MnO 3-c X' c ·(1-r)Li a M1 x M2 y O 2-b X b (in, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, and M2 and M1 do not repeat, X and X' are each independently a halogen capable of replacing at least a portion of the oxygen present in the lithium manganese-based oxide, 0 <r≤0.7、0<a≤1、0≤b≤0.1、0≤c≤0.1、0<x≤1、0≤y<1、0<x+y≤1)。 4. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide is a solid solution of a phase belonging to the C2 / m space group, a phase belonging to the R3-m space group, and a spinel phase belonging to the Fd-3m space group.

5. The positive electrode active material according to claim 4, characterized in that The lithium manganese-based oxide is represented by the following chemical formula 2: [Chemical formula 2] (1-z){rLi2MnO 3-c X' c ·(1-r)Li a M1 x M2 y O 2-b X b }·zLi(Li d Mn 2-d-e M3 e )O 4-g X" g (in, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, and M2 and M1 do not repeat, M3 is at least one selected from Ni, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, X, X' and X" are each independently a halogen capable of replacing at least a portion of the oxygen present in the lithium manganese-based oxide, 0 <r≤0.7、0<a≤1、0≤b≤0.1、0≤c≤0.1、0<x≤1、0≤y<1、0<x+y≤1、0<z≤0.5、0≤d≤1、0<e≤1、0≤g≤0.1)。 6. The positive electrode active material according to claim 5, characterized in that The spinel phase is composed of LiMn 1.5 Ni 0.5 O4 indicates.

7. The positive electrode active material according to claim 1, characterized in that The above-mentioned lithium manganese-based oxide includes: The core is formed by a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group; and a shell portion present on at least a portion of the surface of the core portion and containing a spinel phase belonging to the Fd-3m space group; The core part and the shell part are core-shell particles in which a solid solution is formed.

8. The positive electrode active material according to claim 7, characterized in that The core is a secondary particle formed by agglomeration of a plurality of primary particles. The shell portion exists on at least a portion of the surface of the primary particle.

9. The positive electrode active material according to claim 7, characterized in that The core is a secondary particle formed by agglomeration of a plurality of primary particles. The shell portion exists on at least a portion of the surface of the secondary particle.

10. The positive electrode active material according to claim 7, characterized in that The molybdenum-containing coating is present on at least a portion of the surface of the shell portion.

11. The positive electrode active material according to claim 10, characterized in that The molybdenum-containing coating includes at least one selected from MoO3 and Li2MoO4.

12. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide exists in the form of secondary particles formed by agglomeration of a plurality of primary particles. Molybdenum exists at a higher concentration on the surface of the secondary particle than inside the secondary particle.

13. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide exists in the form of secondary particles formed by agglomeration of a plurality of primary particles. There is a gradient in which the molybdenum concentration decreases from the surface of the secondary particle toward the inside of the secondary particle along the interface between the primary particles.

14. A positive electrode, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 13.

15. A lithium secondary battery, characterized in that: Comprising the positive electrode according to claim 14.